Religious Moderate Education and Cultural Hybridation at Muhammadiyah University - Hadi Pajarianto; Budi Pramono; Puspa Sari; Hajeni Hajeni (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to determine religious moderation education and the existence of cultural hybridization among university students. The subjects of this study were 50 students who were taking ma'had al-jami'a, in semester 2. The data were obtained from the Al-Islam Kemuhammadiyahan course with interviews. This study uses a qualitative approach and utilizes the nVivo 12 plus for data analysis. The results showed that religious moderation education was carried out with the content of national commitment, anti-violence, accommodative to local culture, standard tolerance in the curriculum, and hidden curricula in various learning activities. Moderation and hybridization are traits that will give birth to a moderate character in responding to differences. A moderate approach also produces hybridization through meetings and cultural crosses among participants with diverse backgrounds. The value of moderation in the Al-Islam Kemuhammadiyahan curriculum has designed a hybrid of cultures from diverse ethnicities, religions, and environments. The interdisciplinary implications of the study of religion, education, and sociology are confirmed in this article.